Sejarah Islam di Spanyol: Dualisme Makna antara Penyebaran Agama dan Kolonialisme Islam - Abdul Rahman Matondang; Sufrida Said; Luthfi Luthfi (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2023)
This research aims to analyze the dualism of meaning in the history of Islam in Spain, concerning the spread of Islam and the practices of colonialism that occurred during the Al-Andalus period. The research utilizes a historical approach, drawing on the works of Kuntuwijoyo as the analytical foundation. The research methodology involves a historical analysis of various relevant sources, including historical literature, records, and previous studies. The collected data is then analyzed to understand the historical context, cultural influences, intellectual developments, as well as the impact of the spread of Islam and Islamic colonialism in Spain. The findings of this research reveal a complex dualism of meaning in the spread of Islam and colonialism in Spain. The spread of Islam brought positive changes in culture, art, architecture, science, and language. However, the practices of colonialism also had negative consequences, such as the suppression of non-Muslim groups and suffering during the Reconquista period. This research provides a deeper understanding of the complex dynamics in the history of Islam in Spain. Through a historical analysis, this study uncovers the significant role of Islam in the social and cultural development of Spain while acknowledging the negative impacts of colonialism. The research contributes to understanding the roles of religion, power, and colonialism in the historical context of Spain and its relevance in a broader global context